PENERAPAN REINFORCEMENT UNTUK MENINGKATKAN DISIPLIN PADA SISWA KELAS VII SMP NASIONAL BANAU KOTA TERNATE - Dahri Halek; Andi Suaema (Humano: Jurnal Penelitian, 2023)
This study aims to find out through the application of reinforcement (reinforcement) can improve the discipline of students in the Banau National Middle School class, Ternate City. This research is a class action research (action research class) that consists of four stages, namely action planning, action implementation, evaluation, and reflection. This research was conducted in two cycles. The data analysis technique in this study did not use statistical test analysis but used qualitative descriptive analysis. The results of observations that have been made are processed and analyzed descriptively qualitatively, namely comparing values between cycles and indicators in research. Observations with this qualitative descriptive analysis are based on the results of observations and reflections of each cycle. The results showed that it was known that in the first and second cycles, there was a significant increase in student discipline. from the average value of D (less) in the pre-study to the average value of C (adequate) in the first cycle, with improvements made, the increase in the second cycle is quite significant, namely with an average value of A (very good). However, there are several important notes that must be considered and cannot be resolved in this study in the category of students doing homework.